Zinc and selenium supplementation on treated HIV-infected individuals induces changes in body composition and on the expression of genes responsible of naïve CD8+ T cells function - Osuna-Padilla, Iván Armando; Rodríguez-Moguel, Nadia Carolina; Aguilar-Vargas, Adriana; Tolentino-Dolores, Maricruz; Perichart-Perera, Otilia; Ahumada-Topete, Victor; Ávila-Ríos, Santiago; Soto-Nava, Maribel; Diaz-Rivera, Dafné; De León-Lara, Enrique; Wilson-Verdugo, Marti; Briceño, Olivia (Frontiers in Nutrition, 2024)
Background & aim: Deficiency of zinc and selenium is common in persons living with human immunodeficiency virus (PLWHIV) and has been associated with the development of non-AIDS related comorbidities, impaired immune system function and mortality. Micronutrient supplementation on long-term-treated PLWHIV could bring potential clinical and immunological benefits improving their health status and quality of life. The aim of the present study is to analyze the effect of zinc and selenium supplementation on body composition, bone mineral density, CD4+ T-cell counts, metabolic profile and immune system status on clinical stable PLWHIV on long-term antiretroviral therapy (ART) Methods: This is a randomized pilot clinical trial in which we recruited 60 PLWHIV on ART who were assigned to the intervention groups: zinc (30 mg of zinc gluconate), selenium (200 µg of selenium yeast), zinc + selenium (same doses and presentations) or to a control group (without nutritional supplementation) who received supplementation during 6 months. Primary outcome was defined as changes in body composition (weight, muscle and fat mass and bone mineral density) and secondary outcomes as changes in biochemical and immunological parameters (CD4+ T-cell count, cholesterol, glucose, triglycerides and seric zinc and selenium seric concentrations) before and after supplementation. Peripheral blood mononuclear cells (PBMCs) of one individual of each intervention group were analyzed for single cell transcriptomics before and after supplementation. Results: BMI (p=0.03), fat mass (p=0.03) and trunk fat (p=0.01) decreased after 6 months of selenium supplementation. No changes were observed for cholesterol, glucose or triglycerides after supplementation (p>0.05 in all cases). CD4+ T cells percentage increased after 6 months of selenium supplementation (p=0.03). On the transcriptome analysis, zinc and selenium supplementation induced changes on de expression of genes associated with the function of naive and memory CD8+ T-cells (p<0.05 in all cases). Conclusions: Zinc and selenium supplementation could represent a complementary intervention that may improve the health status and immune response of treated PLWHIV.